How we learn our names is written in the colour of the sky: personing in the Capitalocene - MacDonald, Michael B. (Farol, 2024)
The summer sky is now too often the colour of turmeric. Forest fire smoke, blown in from hundreds of kilometers away, gets stuck like too-wide nets between buildings. Edmonton, Alberta, where I have lived for nearly twenty years is a city on the edge of the Canadian Boreal Forest. It is the largest part of the Taiga, the second largest forest in the world that stretches across Canada and continues across Iceland, Norway, Sweden, Finland, Russia, Mongolia, and Japan. In Canada it covers 270 million hectares between flat prairie and the treeless arctic tundra. The Boreal Forest is the homeland of more than 600 Indigenous communities, most of the known fossil fuel reserves in Canada, it stores more than 208 billion tons of carbon (11% of the world’s total), and along with the Amazon Rainforest is the second of the two great lungs of the world.